2014
DOI: 10.1039/c4ra00769g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the alkali metal cation on the electrocatalytic oxidation of formate on platinum

Abstract: Non-covalent interactions between hydrated alkali metal cations and adsorbed oxygenated species on platinum might considerably inhibit some electrocatalytic reactions. We report in this communication the effect exerted by electrolyte alkali metal cations on the electro-oxidation of formate ions on platinum. The system was investigated by means of cyclic voltammetry and chronoamperometry in the presence of an electrolyte containing Li+, Na+, or K+. As already observed for other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…30 Nakamura et al 34 observed, by infrared spectroscopy, the same OH adsorption rate at potentials below 1.30 V on Au(111) surface regardless the cation, however X-ray diffraction reveled a protective effect against surface roughening at high potentials, this protection being more effective in the presence of Li + than Cs + .…”
Section: Cation Effect On High Order Cyclic Voltammogramsmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Nakamura et al 34 observed, by infrared spectroscopy, the same OH adsorption rate at potentials below 1.30 V on Au(111) surface regardless the cation, however X-ray diffraction reveled a protective effect against surface roughening at high potentials, this protection being more effective in the presence of Li + than Cs + .…”
Section: Cation Effect On High Order Cyclic Voltammogramsmentioning
confidence: 99%
“…Catalytic effects caused by the interactions between cations and O(H) x adsorbed species were recently reported in literature [27][28][29][30][31][32] for several fuel cell reactions. In general, small cations, like Li + and Na + , strongly interact with adsorbed O(H) x,ad , causing the stabilization of these species.…”
Section: Cation Effect On High Order Cyclic Voltammogramsmentioning
confidence: 99%
See 2 more Smart Citations
“…117 Para os picos correspondentes à adsorção de hidrogênio nos terraços, os autores usaram duas funções hiperbólicas inversas, e para os picos correspondentes a adsorção competitiva de H + /OH -nos degraus, os autores usaram uma função gaussiana. A deconvolução de picos sobrepostos na voltametria da platina em meio básico foi uma ferramenta usada também em [118] para estudar o impacto de cátions nas assinaturas voltamétricas. Os autores recorreram a uma função gaussiana única para inferir sobre as diferenças qualitativas nos voltamogramas obtidos na presença de diferentes eletrólitos básicos.…”
Section: Gaussunclassified